A 40-year systematic literature review: about researches of Duan Yucai’s study of the Book of Songs - Qianqian, Zhang; Hiong, Ser Wue (Transnational Press London, 2024)
This study focusses on Qing dynasty scholar Duan Yucai's research on the Book of Songs. Scholars in China from 1984 to 2024 conducted a literature review of related research. This paper uses a systematic literature review method to analyze and discuss existing literature from the three major academic databases over the past 40 years. The results show that the academic community's attention to Duan Yucai's research on the Book of Songs primarily focuses on four areas: general studies on the Book of Songs, phonological studies, exegetical and collation studies, and specific research on Duan Yucai's work Shijing Xiaoxue. According to the study, Duan Yucai made extensive and in-depth contributions to correcting textual errors, analyzing rhyming patterns, and exploring phonetics, all of which play a critical role in these areas. His research on the rhyming patterns of the Book of Songs led to significant advancements in the study of the traditional Chinese rhyme system. Additionally, his work in ancient phonology connected past research with future studies, laying the foundation for subsequent phonological research. Furthermore, Duan Yucai made important contributions to the exegesis and collation of the Book of Songs, particularly in correcting errors, elucidating loan characters, explaining commentaries, and systematically organising content. His method of integrating ancient character studies with the exegesis of the Book of Songs became an important research approach in Qing dynasty scholarship. In his work Shijing Xiaoxue, Duan Yucai's focus on character meanings and phonology played a transitional role in the Qing dynasty, bridging traditional methods with future research methodologies. The article also highlights the limitations of the current research and suggests directions for future studies. For more future research, we could use more recently discovered documents and artefacts, and it could also use the newest discoveries in modern linguistics to help traditional exegetical theories grow.